An analysis of politeness strategies in the comments section of a travel blog - Diyan Ryan Christyan Simbolon; Herman Herman; Bobby Pramjit Singh Dhillon (Lembaga Riset Mutiara Akbar, 2026)
This study analyzes the politeness strategies used in the comment sections of travel-related discussions within the Reddit community r/travel. The research aims to identify the types of politeness strategies applied by users in online interactions. This study employed a qualitative descriptive method based on the politeness theory proposed by Penelope Brown and Stephen C. Levinson, which classifies politeness strategies into bald-on record, positive politeness, negative politeness, and off-record strategies. The data were collected from publicly accessible comments on selected travel-related posts in r/travel and analyzed using data reduction, data display, and conclusion drawing. The findings reveal that all four politeness strategies appear in the data, with positive politeness emerging as the most dominant strategy. This indicates that users tend to create friendly and supportive interactions while discussing travel experiences and recommendations. Negative politeness is used to soften suggestions and disagreements, while bald-on record strategies are applied for direct communication. Off-record strategies appear least frequently and are mainly used for indirect criticism or implied meaning. The study concludes that politeness strategies play an important role in maintaining respectful communication in online travel discussions.